Membership of water user association and implications for food security - Mustapha M. Suraj; Edward Martey; John K.M. Kuwornu; Emmanuel K. Apiors; Francis H. Kemeze; Prince M. Etwire (Journal of Agriculture and Food Research)
Agricultural cooperatives are widely regarded as effective institutions for supporting smallholder farmers, reducing poverty, and improving food security. However, empirical evidence varies with mixed findings across different contexts. This study used a primary data of 820 farm households to examine the relationship between membership of water user association (WUA) and food security, using a quasi-experimental research design. The findings show that WUA membership is significantly influenced by factors including age, marital status, access to extension services, participation in supplementary irrigation (SI) and drought index insurance (DII) initiatives, farm size, and an asset aspiration gap. The results further indicate a positive association between WUA participation and household food security. These findings suggest that rural development policies should focus on strengthening existing WUAs and fostering the establishment of new ones through inclusive approaches that address food insecurity.